A randomized controlled trial of eccentric vs. concentric graded exercise in chronic tennis elbow (lateral elbow tendinopathy). (September 2014) - Peterson, Magnus; Butler, Stephen; Eriksson, Margaretha; Svärdsudd, Kurt
Objective: To analyse treatment effects of eccentric vs. concentric graded exercise in chronic tennis elbow. Design: Randomized controlled trial. Setting: Primary care in Uppsala County, Sweden. Subjects: A total of 120 subjects with tennis elbow lasting more than three months were recruited from primary care and by advertisement. Intervention: Eccentric ( n = 60) or concentric exercise ( n = 60), by lowering or lifting a weight, at home daily, for three months with gradually increasing load. Main measures: Pain during muscle contraction and muscle elongation, as well as strength, was assessed at baseline and after one, two, three, six, and 12 months. Function and quality of life was assessed at baseline and after three, six and 12 months. Results: The eccentric exercise group had faster regression of pain, with an average of 10% higher responder rate at all levels of pain reduction, both during muscle contraction and elongation, ( p < 0.0001 and p = 0.006, respectively). Significant differences were found in Cox's analysis from two months onwards (HR 0.78, 95% confidence interval (CI) 0.63–0.96, p < 0.02). This represents an absolute pain reduction of 10% in the eccentric vs. the concentric group and a number-needed-to-treat of 10. The eccentric group also had a greater increase of muscle strength than the concentric ( p < 0.02). The differences persisted throughout the follow-up period. There were no significant differences between the groups regarding function or quality of life measures. Conclusion: Eccentric graded exercise reduced pain and increased muscle strength in chronic tennis elbow more effectively than concentric graded exercise.